Acquisition of formulaic sequences in intensive and regular EFL programmes. (January 2015) - Serrano, Raquel; Stengers, Helene; Housen, Alex
This paper aims to analyse the role of time concentration of instructional hours on the acquisition of formulaic sequences in English as a foreign language (EFL). Two programme types that offer the same amount of hours of instruction are considered: intensive (110 hours/1 month) and regular (110 hours/7 months). The EFL learners under study are adults at the beginner ( N =35), intermediate ( N =44) and advanced levels ( N =45). A group of native English speakers ( N =12) served as a benchmark. The focus of this study is on the number and range of formulaic sequences the participants used while performing an oral narrative. The results of the statistical analyses show a slight advantage for the learners in the intensive programme, especially at the intermediate level, both in terms of frequency and range of formulaic sequences produced. Moreover, results suggest that there are still marked differences between even the advanced EFL learners in our sample and the native speaker benchmarks, again both in terms of number and range of formulaic sequences.